Effect of n doped amorphous layer between microcrystalline i/n layer on the performance of micromorph tandem solar cells. Issue 1771 (2015) - Yang, Jingjing; Li, Tingkai; Tan, Xueshi; Zhang, Feng; Mao, Bingxue
ABSTRACT: Pin/pin "micromorph" tandem solar cells were manufactured by the industrial production line of Hunan Gongchuang PV Science & Technology Co., Ltd. Based on this kind of solar cells, a n-doped amorphous silicon layer deposited by plasma enhanced chemical vapor deposition technique (PECVD) was inserted between the microcrystalline silicon intrinsic layer and n-doped layer. The result showed that the introduced n-type amorphous silicon layer well improved the solar cells performance by reducing the bad effects caused by microcrystalline silicon growth defects. Compared with the solar cells without inserting the n-doped amorphous silicon layer, the open voltage and efficiency increased remarkably. When the thickness of n-doped amorphous silicon layer is 8nm, the open voltage increased from 72.9V to 73.6V and efficiency increased from 10.63% to 10.74%.